Identification of Cracked Zone in Sutami dam Using Geoelectrical Method - Fina Fitriah; Sunaryo S; Adi Susilo (Department of Physics, Sebelas Maret University, 2015)
We identified the craked zones based on geoelectrical resistivity method in Sutami Dam. There are four lines measurement of geoelectrical resistivity method with a length of 380-400 meters. The direction of each line is from the northeast to the southwest. All of the tracks are located at the top of Sutami Dam i.e. two tracks in the upstream and the others in the downstream. From the analysis we found that the lithology is detected by geoelectrical resistivty method showed two layers of design of Sutami Dam. The two layers that are detected are transition zone and filter zone. Transition zone consists of sandstone rock containing water (0.922 Ωm-9.57 Ωm) and dry sandstone (>9.57 Ωm-320 Ωm). Filter zone consists of sand (>320 Ωm-4410 Ωm). Cracked zones spread in the upstream, downstream, and roadway at the top of Sutami Dam which are indicated by the presence of low resistivity (0.922 Ωm-9.57 Ωm) based on 3D processing of data of geoelectrical resistivity. The distribution of cracked zone indicates that Sutami Dam is susceptible to ground movement.